2022
DOI: 10.1523/jneurosci.2255-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor Cortex GABA Moderates the Relationship between Physical Exertion and Assessments of Effort

Abstract: Experiences of physical exertion guide our assessments of effort. While these assessments critically influence our decisions to engage in daily activities, little is known about how they are generated. We had female and male human participants exert grip force and assess how effortful these exertions felt; and used magnetic resonance spectroscopy to measure their brain GABA concentration. We found that variability in exertion (i.e., the coefficient of variation in their force exertion profile) was associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…Alterations in sensorimotor function have been linked physiological fatigue after 40 min on a bicycle ergometer (Hu et al, 2022) and effort-perception (Zenon, Sidibe, & Olivier, 2015). Specifically, current neurobiological accounts state that fatigue and high effort perception arise when sensory consequences of actions (processed in sensorimotor regions) do not match the proprioceptive prediction (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in sensorimotor function have been linked physiological fatigue after 40 min on a bicycle ergometer (Hu et al, 2022) and effort-perception (Zenon, Sidibe, & Olivier, 2015). Specifically, current neurobiological accounts state that fatigue and high effort perception arise when sensory consequences of actions (processed in sensorimotor regions) do not match the proprioceptive prediction (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that neurotransmitters such as gamma-aminobutyric acid (GABA) and glutamate play a key role in judgments of physical effort and are related to cognitively fatiguing exertion 27,28 . For physical effort, GABA inhibition has been related to changes in descending motor drive and variability in motor output, neural and behavioral signatures that impact feelings of exertion 27 . However, the neurochemical underpinnings of cognitive effort are less straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…Uncertainty arising from this variability may affect the judgment of task performance, leading to inflations in assessment. We have recently showed, in healthy participants, that increased variability serves as an added cost that inflates assessments and valuation of effort 13 .…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that variability in participants’ exertion would disrupt their assessments of effort, and dopamine would decrease both exertion variability and the extent to which variability inflates effort assessments. This hypothesis is motivated by studies showing that increased variability in motor output is associated with increased effort costs 6 , 12 , 13 . During effort assessments, such exertion variability may increase uncertainty in performance outcomes, and disrupt accurate effort assessment.…”
Section: Introductionmentioning
confidence: 99%